Selection for beta 2-microglobulin mutation in mismatch repair-defective colorectal carcinomas. - Bicknell, D; Kaklamanis, L; Hampson, R; Bodmer, W; Karran, P (1996)
Novel peptide antigens complexed with human leukocyte antigen (HLA) and beta 2-microglobulin (beta 2M) molecules are presented at the cell surface to cytotoxic T lymphocytes (CTLs), provoking lysis of the antigen-presenting cell [1]. In tumor cells, genetically altered or abnormally expressed proteins provide a source of peptides that can be presented to CTLs; the resulting anti-tumour CTL responses may provide part of the body's defence against cancer. Disabling mutations in the HLA and beta 2M proteins required for peptide presentation allow a tumour cell to escape destruction by CTLs. Cells with deficient DNA mismatch repair have high spontaneous mutation rates [2] and produce many altered proteins that are a potential source of numerous unique peptides. Mutator tumour cells might therefore be particularly vulnerable to immune surveillance and CTL attack. Mutator phenotypes [3,4] and loss of beta 2M (or HLA) expression [5,6] are both relatively common among sporadic colorectal tumours. We have compared the frequency of beta 2M mutations in sporadic colorectal and other tumours with and without a mutator phenotype. Mutations were more frequent among colorectal tumours with the microsatellite instability indicative of a defect in DNA mismatch repair. The inactivating beta 2M mutations were predominantly frameshifts, which is consistent with the underlying mismatch repair defects. Evasion of immune surveillance by acquiring beta 2M mutations therefore occurs at high frequency in tumour cells with a mutator phenotype due to defective DNA mismatch repair.